Community Interpreting in the Context of Bosnia and Herzegovina - Jurida, Sanel Hadžiahmetović; Pavlović, Tanja (International Journal of Language, Translation and Intercultural Communication, 2016)
The present paper surveys the development and the current position of community interpreting (CI) in Bosnia and Herzegovina (BiH), by providing an insight into the emergence of this “out of necessity” concept. The paper is a reflection of the origins and major features of the profession, from the perspective of active participants in this process. Since the research in this field practically does not exist in BiH, the paper attempts to highlight the fundamentals of the profession, fields of practice, professional organizations and training opportunities. The paper portrays the historical background of CI in the context of BiH, trying to capture the interpreting activities and the accompanying practicalities both in the conflict (1992-1995) and post-conflict periods. CI in BiH is mainly performed my semi- and non-professionals, due to the fact that education and training institutions for community interpreters are traditionally non-existent in this country. The paper brings a historical paradigm into the emergence of the interpreting profession and its inherently embedded international character in BiH. The study of CI may not have such a long tradition as other disciplines, but has immensely gained in popularity in recent decades, particularly in the context of ever-growing interest by scholars. The paper follows these recent global trends aiming at contributing to a more comprehensive research in the field in the context of BiH, highlighting the importance of CI in the evolving society challenged by the newly-emerging social phenomena.